ICS educational module: Cystometry in children. Issue 8 (11th September 2018) - Wen, Jian G.; Djurhuus, Jens Christian; Rosier, Peter F.W.M.; Bauer, Stuart B.
Abstract : Aims: To introduce the standard procedure of cystometry and interpretation of the results in children. Methods: The literature on cystometry in children in PubMed for the last 20 years was reviewed. The updated knowledge regarding indication, preparation, technique, and interpretation of cystometry in children were summarized. Results: Filling cystometry is the core content of a paediatric urodynamic study. In this section, the technique for performing cystometry is introduced in details. Emphasis is placed on correctly setting up the equipment according to ICS and ICCS guidelines, using appropriate terminology, providing indications for its performance with specific considerations for children, and proper interpretation of results. Conclusions: Cystometry can be used in children including newborn to evaluate lower urinary tract dysfunction.